Pembuatan Nanozeolit dari Zeolit Alam Secara Top Down Menggunakan High Energy Milling dan Aplikasinya untuk Penyerapan Ion Fe 3+ - Agusetiani, Lilis (Chem Info Journal, 2013)
Has done research on facbrication nanozeolites from natural zeolite in top down use high energy milling and its application to adsorption Fe3+ Ions. The objective of this research is to fabrication nanozeolites from natural zeolite  in top down using high-energy milling and determine  levels of Fe3+ ions that can be adsorbed by the zeolite usual and zeolite nano. The method  used  in  this  research  for  the  fabrication  nanozeolites  from  natural  zeolites  in  top down using high energy milling. Natural zeolites are sieved using a 225 mesh sieve and then milling  with  high  energy  milling  with  rotational  speed  of  1000  rpm  for  6  hours.  Natural zeolites product milling were activated by HF 1% and NH4Cl 2M. The results of research on natural zeolite pass 225 mesh  sieve, natural zeolite after milling, and natural zeolite milling activation characterized using SEM and   BET  that  indicates  the size of surface morphology with specific surface of 125-250 nm, 75-100 nm, 50-75 nm and 33.997 cm3/g, 29.399  cm3/g, and  86.322  cm3/g,  respectively. Concentration  Fe3+ ions was  analyzed  using AAS with  an optimum  time  of  each  45 minutes,  15 minutes,  and  150 minutes with  the  concentration  of Fe3+ ions are adsorbed were164.98 ppm, 168.65 ppm, and 146.52 ppm